Evaluation of the immunogenicity of a recombinant protein of a Pasteurella multocida isolated from alpacas with pneumonia - Maximiliano G., Jorge (2018)
The aim of the study was to evaluate the in vitro immunogenic activity of a recombinant P6-like protein from a culture of Pasteurella multocida isolated from pneumonia cases in young alpacas. Blood peripheral mononuclear cells (PBMCs) were challenged with a recombinant P6-like protein at a concentration of 10 ng per sample, from 3 to 72 hours. Total RNA was extracted to perform the real-time RT-PCR test to observe cytokine expression levels of the Th1 immune response (TNF-α, IFN-γ and IL-2) and Th2 (IL-10 and IL-4) in the established times. Both Th1 and Th2 profile cytokines expressed a greater number of times than PBMC not exposed to the recombinant protein, where at 24 and 48 hours showed the greater expressions. Likewise, an apparent trend toward the Th2 profile was found, but at levels that did not influence the expression of cytokines in the other profile.